PEGASUS : PENERAPAN TEKNOLOGI MENGGUNAKAN CHEMCOLLECTIVE'S VIRTUAL CHEMISTRY LABORATORY - Rizki Dwi Ningsih; Evelin Natasyah; Sony Ananta; Prima Fitra; Ryrin Novianty; Naila Rahma (Jurnal Pengabdian UntukMu NegeRI, 2019)
PEGASUS (the application of technology using the Chemcollective’s Virtual Chemistry Laboratory) is a process of learning modern techniques by using computer simulations based on understanding chemistry. The purpose of this method is to understand a subject and solve the solution to the limitations or absence of laboratory equipment. The advantage of this simulation method is that access is easy, flexible, safe and does not require expensive fees. The results of the application of Vlab show that it is very helpful for students in understanding chemistry learning especially in lab analysis, this is evidenced from the post test results which are significantly higher than the pretest given at the beginning of the activity so it can be concluded that the application of Chemcollective’s Virtual Chemistry Laboratory is very good for introduced and studied further. Keyword: chemistry, laboratory, simulation, Chemcollective’s